2015
DOI: 10.19030/jabr.v31i6.9467
|View full text |Cite
|
Sign up to set email alerts
|

What Drives Security Issuance Decisions Of Firms Listed On The Johannesburg Stock Exchange: Market Timing Or Dynamic Trade-Off Theory Or Both?

Abstract: This study used the random effects Tobit model to investigate the validity of the market timing, trade-off and pecking order hypotheses of capital structure in 143 non-financial firms listed on the Johannesburg Stock Exchange. The results show that leverage is positively correlated to the modified external finance weighted average market-to-book ratio (EFWAMB). Firm profitability and growth rate are negatively correlated to leverage whilst firm size and asset tangibility are positively correlated to leverage. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 81 publications
(93 reference statements)
0
7
0
Order By: Relevance
“…Consistent with the predictions of the dynamic trade-off theory, Chang and Dasgupta (2009), Dang (2013), Dang et al (2012), Elsas and Florysiak (2011), Flannery and Hankins (2013), Flannery and Rangan (2006) and Qian et al (2009) document a negative correlation between leverage and firm growth rate and NDTs. However, Chang and Dasgupta (2009), Dang et al (2012), Dang (2013), Elsas and Florysiak (2011), Flannery and Hankins (2013), Moyo (2015), Oino and Ukaegbu (2015), Qian et al (2009), Ramjee and Gwatidzo (2012) and Zhou et al (2016) found a negative relationship between leverage and PROF and a positive relationship between leverage and TAN and firm size, which rejects the hypothesis of the dynamic trade-off theory.…”
Section: The Key Firm-specific Determinants Of Capital Structurementioning
confidence: 71%
See 3 more Smart Citations
“…Consistent with the predictions of the dynamic trade-off theory, Chang and Dasgupta (2009), Dang (2013), Dang et al (2012), Elsas and Florysiak (2011), Flannery and Hankins (2013), Flannery and Rangan (2006) and Qian et al (2009) document a negative correlation between leverage and firm growth rate and NDTs. However, Chang and Dasgupta (2009), Dang et al (2012), Dang (2013), Elsas and Florysiak (2011), Flannery and Hankins (2013), Moyo (2015), Oino and Ukaegbu (2015), Qian et al (2009), Ramjee and Gwatidzo (2012) and Zhou et al (2016) found a negative relationship between leverage and PROF and a positive relationship between leverage and TAN and firm size, which rejects the hypothesis of the dynamic trade-off theory.…”
Section: The Key Firm-specific Determinants Of Capital Structurementioning
confidence: 71%
“…In support of the dynamic trade-off theory, Chang and Dasgupta (2009), Dang et al (2012), Dang (2013), Elsas and Florysiak (2011), Flannery and Hankins (2013), Moyo (2015), Oino and Ukaegbu (2015), Qian et al (2009), Ramjee and Gwatidzo (2012) and Zhou et al (2016) found a positive relationship between leverage and TAN and firm size.…”
Section: The Key Firm-specific Determinants Of Capital Structurementioning
confidence: 76%
See 2 more Smart Citations
“…According to the pecking order theory, companies maximise value by systematically choosing to finance new investments with the cheapest available source of funds, which are always internally generated funds called retained earnings, before considering any external financing (Barclay & Smith 2020). Leary and Roberts (2010) and Moyo (2015) argue that where firms face a shortage of internal financial resources and external financial resources appear inevitable, firms prefer debt over equity because of lower information costs associated with debt. Firms will issue shares only as a last resort because the issue of an equity instrument is perceived negatively by the market and the information costs associated with shares are high.…”
Section: Capital Structure Theoriesmentioning
confidence: 99%